2000
DOI: 10.1021/bi992714w
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis and Kinetic Studies of a Plant Cysteine Proteinase with an Unusual Arrangement of Acidic Amino Acids in and around the Active Site,

Abstract: We report the cloning, overexpression, kinetic analysis, and modeling of the tertiary structure of an unusual plant cysteine proteinase. Ananain (EC 3.4.22.31), from Ananas comosus (pineapple) is distinguished from all other cysteine proteinases in the papain superfamily by having a unique combination of acidic amino acids. As well as lacking the acidic residue immediately preceding the active site histidine (position 158 in papain), it also lacks the extensive surface network of acidic residues that were post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…We found the Asp57 residue as the most promising candidate for an essential ionizable residue in contrast with the work of Pinitglang et al, 23 who found Glu50 and Glu35 as the most promising ones. Site-directed mutagenesis results involving a Glu50/Ala mutation in caricain 42 and Glu35/ Ala and Glu50/Ala mutations in ananain 43 practically discarded these residues as essential for catalytic competence (at least in these specific enzymes).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We found the Asp57 residue as the most promising candidate for an essential ionizable residue in contrast with the work of Pinitglang et al, 23 who found Glu50 and Glu35 as the most promising ones. Site-directed mutagenesis results involving a Glu50/Ala mutation in caricain 42 and Glu35/ Ala and Glu50/Ala mutations in ananain 43 practically discarded these residues as essential for catalytic competence (at least in these specific enzymes).…”
Section: Discussionmentioning
confidence: 99%
“…The 17 molecules selected correspond to the following molecules from the 9pap PDB file: 13,16,28,29,40,42,43,97,100,102,135,159,191,203,207,214, and 216. The water oxygen atoms after the refinement step show an average distance of 0.46 Å from their original position in the PDB file.…”
Section: Active Site Water Molecules Contributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, however, evidence has accumulated that this ion-pair can exist at pH values at which the enzyme is not active [15][16][17][18] and that deprotonation of another site on the enzyme is required for papain-like enzymes to become catalytically competent. Several groups have investigated, by site-directed mutagenesis, residues in papain and related enzymes such as caricain (another proteinase from papaya) and ananain [from Ananas comosus (pineapple)] in an attempt to understand the importance of the electrostatic environment to catalysis and to pinpoint single residues which can confer catalytic competence [18][19][20][21]. To date, however, such residues have not been un-…”
Section: Introductionmentioning
confidence: 99%